2007
DOI: 10.1177/1059712307078654
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Mirror Neurons in a Model of Gaze Following

Abstract: Gaze following is the ability to redirect one's gaze to the location where another agent is looking. We present a computational model of how human infants or other agents may acquire gaze following by learning to predict the locations of interesting sights from the looking behavior of other agents through reinforcement learning. The model accounts for many findings about the development of gaze following in human infants. During learning, the model develops pre-motor representations that exhibit many propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Our model previously predicted the emergence of a new class of mirror neurons for gaze-following emerging in its premotor layer [66]. 3 Such kinds of mirror neurons have indeed been recently found in macaque monkeys 4 [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model previously predicted the emergence of a new class of mirror neurons for gaze-following emerging in its premotor layer [66]. 3 Such kinds of mirror neurons have indeed been recently found in macaque monkeys 4 [58].…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed us to replicate a wealth of gaze following phenomena, as discussed throughout the paper. 2 Earlier versions of this model were presented in [37], [39], and [66], with newer versions successfully replicating results for more experimental setups.…”
Section: A Learning Environmentmentioning
confidence: 99%
“…Social context as a driving force for learning has, indeed, been recognized in language learning [59], child development [60] and social cognition [61]. Recently, it has also been suggested that mirror neurons might be the result of reinforcement learning [62][63][64]. Thus, the third loop conceptualizes metacognition as resulting from predictive learning mechanisms that allow for agents to simultaneously learn about the environment as well as about their own internal representations.…”
Section: Beyond Consciousness: Three Predictive Loopsmentioning
confidence: 99%
“…Most of the joint attention approaches in the literature do not explicitly correct for the discrepancy between the head pose and gaze direction, which is reported to be normally distributed with a mean of five degrees in natural settings [36], [37]. In computer graphics literature, there are some recent approaches that model this discrepancy explicitly, in order to synthesize virtual agents with a more natural behavior [30], [38].…”
Section: Outline Of the Methodsmentioning
confidence: 99%